Work based learning no ensino superior: um convite à reflexão sobre o currículo - Genesini, André Gomes (2008)
This is a time of great opportunities and great threats. Technology each time produces more wonders to the senses, things that make life better and more enjoyable. On the other hand, this is the first time in History that man is able to destroy the natural balance of the planet in an irreversible way. The arrival of information technology at the industry in the 1980s demanded a new profile of education for the workers. The damage to the environment can only be avoided through the development of a new kind of sustainable development. This, in turn, requires a new type of professional education. The recent rise of the knowledge economy has placed higher education as a strategical tool to achieve sustainable development. The university must find ways to keep up to the challenge. The key question in this research is how the university can get closer to the world of work and how the learning that occurs in higher education can be more close to the practical needs of the workplace. The objective of this research is to give contributions to the reflection about curriculum through concepts and historical data. This objective is achieved through qualitative analysis, in the form of case study of one of the answers that higher education has given to these challenges: the last generation of Work based Learning curriculums‟. To achieve this goal first was made a bibliographical research of the challenges that higher education faces and, specially, of Work based Learning. This research was the basis to the planning and implementation of a Work based Learning project to be used as case study in the research. The analysis of the data, in the light of the bibliographical research, suggests that Work based Learning generates a learning that is more closely related to the needs of the workplace and that Work based Learning equips more efficiently the students to succeed in the workplace